The mediation and moderation effects of stress and social support on leadership-organizational citizenship behavior relationship: A study among bank employees in Malaysia - Soo, Hooi Sin (2012)
This study proposed a mediated-moderation model to examine the relationship between leadership and organizational citizenship behavior (OCB) because the mechanism of how leadership influence employee OCB is not sufficiently clear. Besides examining the direct relationship between leadership and OCB among 474 bank employees from a total of 60 bank branches in Penang, the study also investigated the indirect relationship with the inclusion of stress as a mediator and social support as a moderator in the relationship between leadership and OCB. Finally the examination of the mediated-moderation effects of leadership, stress and social support and its influence on OCB was also undertaken. A survey was conducted using a questionnaire through self-administered approach and the data were obtained from employee’s self-ratings. Multiple regression analysis and hierarchical multiple regression analysis were used to analyze the data. The results indicated that stress mediates the relationship between leadership and OCB, and that social support moderates the relationship between leadership and stress. Finally, an ANOVA was undertaken to examine the mediated-moderation effect and the results indicated that employees with higher social support have lower stress experience from the leader and this leads to higher OCB. The findings of this study suggest that different types of leader behaviors can influence different symptoms of stress among employees. However this effect can be mitigated by adequate social support. The implication of this research is that managers need to be aware that their leadership style should not unduly induce stress among their employees as this can have a deleterious effect on OCB. Further management must develop a supportive social environment through social network as this has been shown to buffer stress among employees.